FRI0330 Predictivity of Ocular Surface Parameters and Tear Protein Expression in The Diagnosis of Sjögren Syndrome versus Dry Eye. (15th July 2016) - Vukatana, G.; Versura, P.; Trevisani, M.; Giannaccare, P.; Buffa, A.; Mulè, R.; Corvaglia, S.; Rossi, E.; Malavolta, N.
Abstract : Background: Several studies report alterations of protein expression profiles of inflammatory cytokines in the tears of patients with dry eye syndrome. Futhermore several non cytokine proteins such as lysozyme, lactoferrin, lipocalin, etc were found to be altereted too (1). The minimal invasiveness of the methods of sample collection using glass microcapillary tubes makes tear fluid very interesting option for proteomic studies, although analysis may be challenging because of the small volume of tear fluid (>5nl) that can be collected (2). Objectives: to discriminate the difference between ocular surface parameters and protein expression in tears of patients with dry eye syndrome and patients affected by Sjögren syndrome. Methods: 80 patients (female 77) with sicca syndrome arrived in a period included from September 2010 to May 2015, in our Rheumatologic Unit were evaluated. Break Up time (BUT), Schirmer and Jones test, fluorescin and green lisamin coloration, citologic analysis of conjuctive for scraping/impression was done in each patients to evaluate the ocular surface parameters. 5 nl of tear fluid, was collected on external angle by using a glass microcapillary tube. The tear fluid sample was then analysed by Agilent 2100 Bioanalyzer system to detect non cytokine protein patterns. Scintigrafic parameters for salivary gland impairment, ANA, ENA, rheumatoid factor and albumin was researched too. The sensibility, the specificity and the predictive value (PV+ and PV -) was calculated for each protein evaluated. Statistic analysis was performed by using SPSS 20.0 IBM, Mann-Whitney test for indipendent samply and ROC curve. Results: 25/80 patients was affected by Sjögren syndrome according to Vitali Criteria of 2002. Demografic and laboratoristic data of both groups were calculated. Significant reduction of BUT, fluorescin and green lisamin coloration value were observed in patients with Sjögren syndrome versus patients with dry eye. Significant reduction of lipocalin and lysozyme concentration were evaluated in patients affected by Sjogren syndrome versus the dry eye group. Lipocalin and fluorescin coloration risult having a high predictive value to discreminate patiens affected by Sjogren syndrome from patient with dry eye. Conclusions: Protein pattern alterations in tears represent a high potential to generate biomarkers for disease state determination and provide sources for new diagnostic procedures and treatment response. In this study the observed reduction of lipocalin concentration and fluorescin coloration value was determinant to distinguish patients affected by Sjögren syndrome from patients with dry eye. References: Boehm N. Alterations in the tear proteome of dry eye patients a matter of the clinical phenotype. 2013 Invest. Ophtamol. Vis. Sci. 54, 2385–2392 Li N. Characterization of human tear proteome using multiple proteomic analysis techniques. 2005 J Proteome Res 4, 2052–2061 Disclosure of Interest: None declared